2017
DOI: 10.3762/bjnano.8.74
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of graphene–transition metal oxide hybrid nanoparticles and their application in various fields

Abstract: Single layer graphite, known as graphene, is an important material because of its unique two-dimensional structure, high conductivity, excellent electron mobility and high surface area. To explore the more prospective properties of graphene, graphene hybrids have been synthesised, where graphene has been integrated with other important nanoparticles (NPs). These graphene–NP hybrid structures are particularly interesting because after hybridisation they not only display the individual properties of graphene and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(47 citation statements)
references
References 335 publications
(342 reference statements)
0
47
0
Order By: Relevance
“…In last 10 years, a number of methods are developed for graphene synthesis by researchers. Most common techniques are Mechanical exfoliation [38], chemical synthesis [46], chemical exfoliation [47] [48], epitaxial growth [49], and thermal chemical vapor deposition (CVD) [50]. The bottom-up approach is more accurate and practical than the top-down approach as this is capable of producing nanostructures with less imperfections and better chemical composition along with its ability for mass production in large quantities [54] [55] [56].…”
Section: Synthesis Of Graphene: Fabrication Methodsmentioning
confidence: 99%
“…In last 10 years, a number of methods are developed for graphene synthesis by researchers. Most common techniques are Mechanical exfoliation [38], chemical synthesis [46], chemical exfoliation [47] [48], epitaxial growth [49], and thermal chemical vapor deposition (CVD) [50]. The bottom-up approach is more accurate and practical than the top-down approach as this is capable of producing nanostructures with less imperfections and better chemical composition along with its ability for mass production in large quantities [54] [55] [56].…”
Section: Synthesis Of Graphene: Fabrication Methodsmentioning
confidence: 99%
“…Large‐bandgap quantum dots like CdS and ZnO were also integrated with graphene to form hybrid phototransistors, showcasing promising applications in UV detectors and image sensors with high sensitivity and gain of 10 7 –10 9 . In a recent review, various transition metal oxide (TMO) nanoparticles were also used in conjunction with graphene for different applications. Lee et al reported graphene–perovskite (CH 3 NH 3 PbI 3 ) hybrid phototransistors, which exhibited a responsivity of 180 A W −1 in the UV‐vis range, limited by the absorption range of the perovskite layer .…”
Section: D‐based Photodetectorsmentioning
confidence: 99%
“…Hybrid-or composite-materials of zinc (II) oxide (ZnO) and graphene (or, often, reduced graphene oxide) are currently of great interest in the materials science community because they are inexpensive, non-toxic, and boast a spectrum of useful applications [1][2][3]. Creating strong electronic interaction between nanoscale graphene and ZnO in a composite can significantly modify the ZnO band structure, leading to an array of exciting new properties for the bulk material.…”
Section: Introductionmentioning
confidence: 99%
“…The clean decomposition pathways of various metal oxalates have been documented for decades [37,38]. Utilizing any of these should allow for syntheses of composites with nearly any metal oxide in any stoichiometry [2], allowing for tuning of the band structures of these materials. This is, however, the subject of ongoing research.…”
Section: Introductionmentioning
confidence: 99%